Integrated serum metabolomics and network pharmacology reveal molecular mechanism of Qixue Huazheng formula on peritoneal fibrosis - Xiaohui Meng; Xiaohui Meng; Li Sheng; Yongqing You; Yongqing You; Huibo Dai; Manshu Yu; Funing Wang; Funing Wang; Ziren Zhou; Ziren Zhou; Yun Shan; et al. (Frontiers in Pharmacology)
BackgroundPeritoneal fibrosis (PF) causes peritoneal dialysis (PD) withdrawal due to ultrafiltration failure. Qixue Huazheng formula (QXHZF), comprising Astragalus membranaceus, Centella asiatica, and Ligusticum sinense, is applied to treat PD-related peritoneum injury related; however, the active components, core genes, and underlying mechanism involved remain unclear.MethodsThe anti-PF effects of QXHZF were verified in vivo and in vitro. Targets underlying QXHZF-mediated improvement of PD-induced PF were predicted using network pharmacology analysis. Metabolites associated with QXHZF treatment of PD-related PF were analyzed by serum metabolomics. Integration of network pharmacology and serum metabolomics findings identified potentially important pathways, metabolites, and targets, and molecular docking studies confirmed the interactions of key components and targets. Western blotting (WB), quantitative real-time PCR (qRT-PCR), TdT-mediated dUTP Nick-End Labeling (TUNEL) staining, and flow cytometry were conducted.ResultsQXHZF had potent therapeutic efficacy against PF according to WB, qRT-PCR, and pathological section examination. Network pharmacological analysis indicated that multiple QXHZF compounds contributed to improving PF by modulating various targets and pathways. Differential metabolites were identified by serum metabolomics analysis. Integrated data analysis indicated that steroid hormone biosynthesis, the Ras signaling pathway, apoptosis, and estrogen signaling contributed to the effects of QXHZF. Metabolite-target network and molecular docking analyses revealed that QXHZF can bind to estrogen receptor 1 (ESR1) and rapidly accelerated fibrosarcoma 1 (RAF1) through its components. WB demonstrated that QXHZF treatment reversed activation of the above-mentioned signaling pathways, thereby inhibiting PD fluid-induced PF.ConclusionQXHZF can significantly ameliorate PD-induced PF and may regulate estrogen signaling, the Ras pathway, and apoptosis in this context.